Analysis of Kendal Industrial Estate (KIK) impact on the Surrounding Air Quality - Cholis, Muhammad Ridwan Nur; Yulianti, Ian; Fianti, Fianti (Physics Communication, 2023)
The Kendal Industrial Area (KIK) is developed to accelerate economic development in the Kendal district area and to support the acceleration and expansion of economic development. Industrialization will lead to a process of air pollution which is marked by 16 companies that are already operating in the KIK area. This research was aimed to analyze the impact of the Kendal Industrial Estate on air quality. The approach of this research used descriptive method, with an analysis of changes in air quality that occurred before the existence of KIK and after the development of industrial areas. The factors that affect the air quality conditions reviewed in this study were air temperature, surface pressure, wind speed, and relative humidity. Data collection techniques used were secondary data NASA satellite imagery. The results showed that there is a change in air conditions after the presence of KIK as indicated by the increase in air pressure and air temperature and the decrease in relative humidity and wind speed. The results indicates that the existence of the Kendal Industrial Area (KIK) causes changes in environmental conditions, but these changes are not significant so they are still within the comfort limits for industrial areas.